Identifying Dynamic Membrane Structures with Atomic-Force Microscopy and Confocal Imaging. (13th February 2014) - Timmel, Tobias; Schuelke, Markus; Spuler, Simone
Abstract Combining the biological specificity of fluorescence microscopy with topographical features revealed by atomic force microscopy (AFM) provides new insights into cell biology. However, the lack of systematic alignment capabilities especially in scanning-tip AFM has limited the combined application approach as AFM drift leads to increasing image mismatch over time. We present an alignment correction method using the cantilever tip as a reference landmark. Since the precise tip position is known in both the fluorescence and AFM images, exact re-alignment becomes possible. We used beads to demonstrate the validity of the method in a complex artificial sample. We then extended this method to biological samples to depict membrane structures in fixed and living human fibroblasts. We were able to map nanoscale membrane structures, such as clathrin-coated pits, to their respective fluorescent spots. Reliable alignment between fluorescence signals and topographic structures opens possibilities to assess key biological processes at the cell surface such as endocytosis and exocytosis.